2009
DOI: 10.1128/aem.00119-09
|View full text |Cite
|
Sign up to set email alerts
|

Zoosporic Tolerance to pH Stress and Its Implications for Phytophthora Species in Aquatic Ecosystems

Abstract: Phytophthora species, a group of destructive plant pathogens, are commonly referred to as water molds, but little is known about their aquatic ecology. Here we show the effect of pH on zoospore survival of seven Phytophthora species commonly isolated from irrigation reservoirs and natural waterways and dissect zoospore survival strategy. Zoospores were incubated in a basal salt liquid medium at pH 3 to 11 for up to 7 days and then plated on a selective medium to determine their survival. The optimal pHs differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
1
36
0
2
Order By: Relevance
“…La mayoría de las especies de Phytophthora son favorecidas por alta humedad, temperaturas entre 15 y 35 °C, climas húmedos con lluvias abundantes y sustrato o suelo pobres en nutrientes. Cuando se presenten estas condiciones, es recomendable analizar muestras del sustrato o suelo para detectar al patógeno (Erwin y Ribeiro, 1996;Drenth y Sendall, 2001;Kong et al, 2009). …”
Section: Vegetable Trap Tissuesunclassified
See 1 more Smart Citation
“…La mayoría de las especies de Phytophthora son favorecidas por alta humedad, temperaturas entre 15 y 35 °C, climas húmedos con lluvias abundantes y sustrato o suelo pobres en nutrientes. Cuando se presenten estas condiciones, es recomendable analizar muestras del sustrato o suelo para detectar al patógeno (Erwin y Ribeiro, 1996;Drenth y Sendall, 2001;Kong et al, 2009). …”
Section: Vegetable Trap Tissuesunclassified
“…Most species of Phytophthora are favored by conditions of high humidity, temperatures between 15 and 35 °C, humid climates with abundant rains and nutrient-poor substrate or soil. When these conditions are present, it is advisable to analyze samples of the substrate or soil to detect the pathogen (Erwin and Ribeiro, 1996;Drenth and Sendall, 2001;Kong et al, 2009). It is suggested that the collections are made from moist soil, near apparently healthy roots and from those that are growing (Erwin and Ribeiro, 1996;Balci et al, 2007;Fichtner et al, 2007).…”
Section: Isolation Of Soil Phytophthora or Planting Substratementioning
confidence: 99%
“…DO differences were within 2 mg/L for most sampling dates, which may not change DO conditions in RIRs from being unfavorable for pathogen survival. Survival rates for zoospores of seven Phytophthora species were pH dependent [10]. Most pH differences were within 1.0 unit in RIRs and would likely to have little effect on pathogen survival.…”
Section: Discussionmentioning
confidence: 87%
“…Phosphorous becomes less available to the plants when pH is above 7.2 [3]. Water temperature (T) [4][5][6][7][8][9], pH [10], dissolved oxygen (DO) [11], EC [12] and oxidation-reduction potential (ORP) [13] also affect the survival and growth of plant pathogens in the same reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pH level fluctuations in aquatic systems influence the dissemination of many Phytophthora species from a single point of infection to far distance points (Gibbs et al 1999;Hong and Moorman 2005;Kong et al 2009). In this view, effects of pH on the survival and growth of the pathogen are of great importance.…”
Section: Discussionmentioning
confidence: 99%